Case Marking System in Khaling - Rai, Arjun (Kirat Pragya किरात प्रज्ञा, 2025)
This study examines the case-marking system in Khaling, a Rai-Kiranti language, and compares it with related languages such as Koyee, Sampang, Bantawa, Bayung, Dumi, Thulung, and Mewahang. Khaling follows an ergative-absolutive alignment, where the absolutive case remains unmarked, while the ergative and instrumental cases share the same marker (<-ʔɛ/-a>). The dative case is marked by <-bi>, while the genitive case takes <-po>. Other cases, including locative (<-bi>), Comitative (<-kolo>), ablative (<-lʌ/-kʌ/-lʌkʌ>), and allative (<-tʰʌ>), show both shared patterns and language-specific variations. The comparison reveals that while some Kiranti languages exhibit consistent case-marking strategies, others display phonetic and morphological divergence. Many languages use -bi/-pi for locative and -lʌ/-la for ablative, but differences in dative and allative markers suggest independent linguistic evolution. Some languages leave the dative unmarked, while others, like Bantawa and Dumi, use -lai. The findings highlight Khaling's historical connections with other Kiranti languages while showcasing distinct grammaticalization patterns. This study contributes to a broader understanding of case systems and linguistic evolution in the Kiranti languages.